Redesigning of a Primary school - Saleem Sirra; Alaa Ibreigheth; Fadi Nazzal (My University, 2016)
The project presents an integrative design of a school. It contains of three stories. We think, that the shortage of school in this area, and a big number of children encourages us to choose this project as a graduation one. Above all, we believe that the children have the right to learn, and no child is left behind. In addition, presence of vital infrastructure in this area can give a continuity for this project.  The main objective of this project is to create an integrated design for the School. To say, it includes architectural design, structural system, mechanical, environmental, electrical and safety aspects.   The project will be started with the definition and the significance of the project. Then the problems and their resolution will be discussed in details. Moreover, standard and experimental methods are explored properly. Finally, the results will be taken into consideration in solving problems and then well begin the project

, ,         . :   . .
Redesigning of a Primary school